EVALUASI DAN REMIDIASI DALAM PEMBELAJARAN BAHASA DAN SASTRA MULTILITERASI - Fadli, Rusli Ilham (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Hasyim Asy'ari (Unhasy), 2018)
ABSTRAKMultiliteration is currently a learning method that has been developed by teachers, whopreviously used literacy that only read and write less widely, currently multiliteration of students candevelop ways of reading and using various internet media and free media. Multiliteration remains to readand write. In reading students must have a septetap concept to read and write. In reading students musthave a septetap concept to read and write. In reading students must have criteria such as characters, taste,creativity, and desire, which allows each reader.Indonesian language learning has a very important role not only for communication and alsofor the benefit of mastering science. According to Ghazali (2010: 168) language learning is